Using the Reaction Rate Learning Module with a STEM Approach to Student’s Creative Thinking Ability - Afadil; Sitti Rahmawati; Wahda Nur Alisa; Kasmudin Mustapa (Universitas Pendidikan Ganesha, 2023)
Creativity is one of the competitiveness in the 21st century. The problems faced by many students are that they do not understand the material in the handbook which causes low creative thinking skills, one of the alternatives in learning this century is the STEM approach. This study aims to determine students' creative thinking skills using the reaction rate learning module with the STEM approach through Google Classroom. The type of research used was pre-experimental with one group pretest-posttest design. Data on the results of students' creative thinking abilities were taken using a creative thinking test given before and after learning. The results showed that students' creative thinking abilities After implementing the reaction rate learning module with the STEM approach through Google Classroom, students' creative thinking abilities in aspects of fluent and original thinking were in the very high category, while the flexible and detailed thinking category was in the high category with an average presentation of the four aspects are in the high category, namely 67.1% and the average N-Gain value of 0.59 is in the medium category. It can be concluded that there is an increase in students' creative thinking skills.